Increased functional properties and thermal stability of flexible cellulose nanocrystal/ZnO films. (20th January 2016) - Lizundia, E.; Urruchi, A.; Vilas, J.L.; León, L.M.
Graphical abstract: AFM image showing surface topography of flexible cellulose nanocrystal/ZnO films with improved functional properties upon ZnO loading. Highlights: Renewable cellulose nanocrystal (CNC)/ZnO films have been synthesized. A closely packed CNC network is achieved using solely water as dispersing agent. Ultraviolet light is blocked by 98.5% while good transparency is maintained. Thermal activation energy is increased by 141% with the addition of 5 wt.% ZnO. Structural integrity of CNC/ZnO nanopapers is maintained over the −125 to 225 °C range. Abstract: In this work we attempt to improve the functional properties and thermal stability of cellulose nanocrystal (CNC) films by means of eco-friendly materials and processes. Mechanically flexible films of closely packed CNCs with concentrations up to 5 wt.% of zinc oxide (ZnO) nanoparticles have been prepared by a simple, standard and environmentally friendly method using solely water. Results reveal that ultraviolet light is blocked by 98.5% at 1 wt.% ZnO while good transparency is maintained. A sharp hydrophobicity increase is observed with the addition of ZnO which would enhance the durability of films by decreasing the water diffusion through the material. The thermal degradation activation energy ( E ) presents an increase of 141%, denoting a high thermal stability of films, which would result beneficial for their potential application in the field of flexible electronics. Mechanical results demonstrate a high structural integrity of CNC/ZnO as a result of the occurring strong cellulosic inter- and intramolecular interactions within the closely packed CNC network. In overall, this work highlights the potential for environmentally friendly processing of sustainable nanostructured functional materials based on cellulose.